Integrasi Nilai Islam dalam Pendidikan: Studi Kasus Pelatihan Guru Mata Pelajaran Umum pada Madrasah Tsanawiyah - Supriadi, Udin; Faqihuddin, Achmad; Islamy, Mohammad Rindu Fajar (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Islamic education in Madrasah Tsanawiyah in Bandung City faces the challenge of integrating Islamic values in the general curriculum. To address this issue, this community service program aims to train general subject teachers in integrating Islamic values into daily learning. The activity involved 70 teachers and used interactive training methods, including workshops and group discussions. The focus of the training was on improving teachers' understanding and skills in applying Islamic values, such as honesty, justice, and cooperation, into subjects such as math, science, and social studies. The results of the program showed a significant improvement in teachers' ability to integrate Islamic values effectively, which contributed to stronger student character building. The activity also identified some challenges in implementing the integration of Islamic values, such as limited time and resources. Therefore, continued support and additional resources are needed to ensure the sustainability of this program. The impact of this service program is expected to make a meaningful contribution to improving the quality of Islamic education in Madrasah Tsanawiyah Bandung City and can be replicated in other schools.